2020
DOI: 10.1259/bjr.20200319
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ionising radiation on the phenotype of bone marrow-derived extracellular vesicles

Abstract: Objectives: Ionising radiation-induced alterations affecting intercellular communication in the bone marrow (BM) contribute to the development of haematological pathologies. Extracellular vesicles (EVs), which are membrane-coated particles released by cells, have important roles in intercellular signalling in the BM. Our objective was to investigate the effects of ionising radiation on the phenotype of BM-derived EVs of total-body irradiated mice. Methods: CBA mice were irradiated with 0.1 Gy or 3 Gy X-rays. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…It has been shown that whole body irradiation influences the secretion of EVs from bone marrow cell subpopulations in mice: EVs containing mesenchymal stem cell markers CD29 and CD44 decreased, while EVs with haematopoietic stem cell or lymphoid progenitor markers increased after irradiation (Kis et al 2020 ). Several studies suggest increased EV release after irradiation in in vitro and in vivo models.…”
Section: Out-of-field Effects: Model Systems and Mechanismsmentioning
confidence: 99%
“…It has been shown that whole body irradiation influences the secretion of EVs from bone marrow cell subpopulations in mice: EVs containing mesenchymal stem cell markers CD29 and CD44 decreased, while EVs with haematopoietic stem cell or lymphoid progenitor markers increased after irradiation (Kis et al 2020 ). Several studies suggest increased EV release after irradiation in in vitro and in vivo models.…”
Section: Out-of-field Effects: Model Systems and Mechanismsmentioning
confidence: 99%
“…We also demonstrate the utility of urinary EVs as an effective source of biomarkers for detecting IR exposure. Previous reports have studied whole urine, whole plasma, and plasma EVs as sources for biomarkers of IR exposure and IR damage (3,11,(28)(29)(30)(31). Dyslipidemia has previously been observed after radiation exposure (3,12,(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…For transmission electron microscopy (TEM) analysis, EVs were processed as described in [ 31 ]; namely, samples were applied to formvar-coated nickel grids and stained with 2% uranyl acetate ( v / v ) solution for 5 min. Grids were air-dried and viewed using a JEOL TEM 1011 TEM (JEOL, Peabody, MA, USA) operated at 80 kV.…”
Section: Methodsmentioning
confidence: 99%